DAMPAK PACARAN SECARA HOLISTIK TERHADAP REMAJA - Hikmah; Sekar Ayu Utami, Arifah; Sholikah, Iis (Jurnal Media Ilmu Kesehatan, 2014)
This study aims at knowing the impact of going to the physical, psychological, social, spiritual (holistic ) in class X and XI in MAN 1 Wates in 2013. The reason this research because the results obtained from in- depth interviews in 4 students MAN 1 Wates lack of knowledge about the courtship activities and impact so there are irregularities in the reproductive organs as well as the impact of physical,  psychological,social and spiritual students. The method used by the Qualitative Quantitative Descriptive sampling technique used "Simple Random Sampling". Quantitative respondents in this study were students of class X and XI as many as 181 people, while respondents in-depth qualitative interviews with as many as 4 people. The results showed that there is going to impact as much as 75.2 % physical, 74% psychological, social as much as 73.5 %, 76.7 % and spiritual as much as 52.5 % holistic impact. For MAN 1 Wates is expected to provide the facilities and infrastructure to provide information on reproductive health knowledge and prevention of courtship holistic impact both on the parents and to the students directly through counseling and peer group . Keywords : Impact Courtship, Physical, Psychological, Social, Spiritual